1993
DOI: 10.1007/bf01972716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-inflammatory compounds on edema formation and myeloperoxidase activity in the arachidonic acid-induced ear model in the mouse

Abstract: The arachidonic acid (AA)-induced ear edema model in the mouse has been demonstrated as an effective in vivo experimental tool to screen compounds showing anti-inflammatory activity. Since neutrophil influx is a component of the inflammatory reaction, we have modified this assay by quantitating myeloperoxidase (MPO) levels which reflect neutrophil accumulation in the edematous biopsies of the mouse ear. Our work has shown that orally administered 5-lipoxygenase inhibitors, dual inhibitors (CO/LO), and steroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…These results indicate that LOX metabolites are mainly involved in this inflammation model, and the potent anti-inflammatory activity of ER-34122 can be ascribed to its inhibition of LOX products generation. Our results showing lack of inhibitory activity of indomethacin in the ear inflammation model are consistent with the findings of Griswold et al [33,43] and Kotyuk et al [44]. However, these results, including our results, are not consistent with the findings of Crummey et al [41] and Carlson et al [42] that topical administration of indomethacin and/or naproxen inhibited edema formation in the ear inflammation.…”
Section: Discussionsupporting
confidence: 67%
“…These results indicate that LOX metabolites are mainly involved in this inflammation model, and the potent anti-inflammatory activity of ER-34122 can be ascribed to its inhibition of LOX products generation. Our results showing lack of inhibitory activity of indomethacin in the ear inflammation model are consistent with the findings of Griswold et al [33,43] and Kotyuk et al [44]. However, these results, including our results, are not consistent with the findings of Crummey et al [41] and Carlson et al [42] that topical administration of indomethacin and/or naproxen inhibited edema formation in the ear inflammation.…”
Section: Discussionsupporting
confidence: 67%
“…Considering the inhibitory effect of AA on pefloxacin-induced tendon lesions in the present study, we suspect that leukotrienes, which are 5-LO products, play a role in the development of the lesion. Kotyuk et al (13) reported that acid-induced ear edema in mice was prevented by treatment with dual CO-LO inhibitors, 5-LO inhibitors, and steroids but not with CO inhibitors. Similar effects by the LO or the CO inhibitor were demonstrated in brain edema in rats (3).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils migrate into the dermis of the ear 30 min after AA-application and reach the maximum concentration 1 h when edema culminates. The quantity of polymorphonuclear leukocytes (PMNL) migrating into the inflammatory sites corresponds to the degree of development of edema [10,11] . 5-LOX inhibitors are known to reduce the development of edema in mice [12] .…”
Section: Pharmacologymentioning
confidence: 99%
“…The development of the ear edema was calculated by subtracting the thickness of the left ear (vehicle control) from that of the right ear (treated ear). The percentage inhibition was calculated according to Kotyuk [11] .…”
Section: Antiinflammatory Activity In the Aa Induced Mouse Ear Edemamentioning
confidence: 99%